E-commerce and the organisation of the marketing function. (1st January 2002) - Bennett, Roger; Koudelova, Radka
Heads of marketing in 91 UK companies with electronic marketing facilities participated in a survey designed to investigate relationships between marketing personnel and staff responsible for the technical side of their firms' e-commerce operations. The research focused on the possible organisational consequences of the introduction of electronic marketing; whether frictions and conflicts arose between marketing managers and e-commerce specialists; and respondents' perceptions of the contributions of e-commerce to the marketing function. Results indicate that many of the organisational consequences experienced during earlier implementations of major IT-related new technologies have been repeated in the e-commerce field. Marketing executives reported that IT experts increasingly occupied highly influential roles in their companies' marketing decision-making systems. This raises the (undesirable) prospect of key marketing policies being determined by people who lack the general business knowledge necessary to manage the marketing function within an e-commerce context or to integrate marketing with e-commerce in the most effective ways.